The Effect of Video-Based Flipped Classroom Strategy on Learning Outcomes and Students’ Active Participation - Moch Dicky Riza; Muhamad Aris Sunandar; Siti Fatimah Abd. Rahman (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The flipped classroom model has gained significant attention as an innovative pedagogical approach, particularly in enhancing student engagement and learning outcomes. This study investigates the effectiveness of a video-based flipped classroom in improving students' academic performance and active participation during in-person classes. The research employed a quasi-experimental design, with two groups: one experiencing the flipped classroom approach, and the other following traditional lecture-based instruction. Data were collected through pre- and post-tests to assess learning outcomes, as well as an observation rubric to measure student participation. Results indicated that the flipped classroom group showed a 17% improvement in learning outcomes compared to the traditional group. Furthermore, the flipped classroom group exhibited twice the level of active participation, as measured by the rubric. These findings suggest that the flipped classroom model is effective in fostering a more interactive and participatory learning environment, where students engage with content before class and apply their knowledge through discussions and problem-solving activities during in-class sessions. The study also highlights the importance of video-based learning in preparing students for active participation and the role of the teacher as a facilitator in flipped classrooms. Despite the promising results, the study acknowledges several limitations, including reliance on technology and students' readiness for independent learning. The study concludes with recommendations for teacher training and future research to further explore the effectiveness of flipped classrooms across diverse educational contexts.